Exploring legal‐ and health‐risk messaging to reduce demand for elephant skin - Beilu Duan; Zac Posada‐Baynham; Joceline Yong; Xiaoxi Zhang; Zhan Chen; Anita K. Y. Wan; Jingjing Zhao; Alexander Clark; Lishu Li; Wuji Zheng; Tien Ming Lee (Conservation Biology, 2026)
Asian elephants ( Elephas maximus ) are poached for an illegal trade in their skins, which are used in traditional medicine in Africa and Asia. We explored whether messages about the legal and health risks of using elephant skin for medicinal purposes (stomach illness) could reduce such consumption. We conducted a randomized controlled trial intervention experiment based on a health belief model. We showed 1673 residents at China's Yunnan–Myanmar border comic strips that portrayed these risks (legal‐risk and health‐risk treatments and control). Respondents were then asked for their perception of benefits and risks of using elephant skin and their consumption intentions for treating stomach illness (i.e., seek elephant skin, seek animal‐based traditional medicine, visit informal market, and visit hospitals). We used structural equation models to examine whether and how different messages affect consumption intentions. Compared with the control group ( n = 580), the comics that showed the legal risks of use of elephant skin ( n = 529) significantly reduced respondents’ intentions to seek elephant skin by 24% compared with the control group, particularly when the message conveyed that its use is not a cure. The health‐risk treatment ( n = 564) increased respondents’ intentions to go to the hospital when suffering from stomach illness and, unexpectedly, increased the intention of urban residents who had never heard of elephant skin as a treatment to look for it by 40% compared with those of urban residents in the control group. Our results revealed that interventions tailored to specific audience segments are necessary to prevent unintended, negative consequences of public messaging conservation interventions.